Syariah Security Crowdfunding: A Risk Analysis for Alternative Funding Solution for Indonesian Small and Medium Enterprises - Alfarisi, Mochammad Salman; Hannase, Mulawarman (Journal Of Middle East and Islamic Studies, 2024)
Micro, Small and Medium Enterprises (MSMEs) are currently a sector that plays an important role in increasing economic stability in Indonesia. However, one of the crucial obstacles related to the development of micro businesses is limited capital and low access to sources of capital. Sharia securities crowdfunding is a form of innovation in the field of financial technology that offers alternative solutions for MSME players in obtaining funding. However, sharia securities crowdfunding is not without risk analysis. Some of the other risks of crowdfunding are inadequate regulatory and regulatory frameworks, low public awareness and trust, and the risk of dehumanization that has potential to occur in crowdfunding due to a lack of communication between fundraisers and funders. Meanwhile, the advantages of investing in Sharia SCF are that there is no collateral obligation to obtain funding, easier access to capital, and companies and investors can monitor the progress of the Crowdfunding being carried out. Sharia securities crowdfunding is also considered the best alternative when SMEs struggle to have access to traditional funding, this is because crowdfunding is able to provide speed and accessibility.